2003
DOI: 10.1242/jcs.00665
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumapical membrane antigen 1 (PfAMA-1) is translocated within micronemes along subpellicular microtubules during merozoite development

Abstract: During the assembly of Plasmodium falciparum merozoites within the schizont stage, the parasite synthesizes and positions three sets of secretory vesicles (rhoptries, micronemes and dense granules) that are active during red cell invasion. There are up to 40 micronemes per merozoite, shaped like long-necked bottles, about 160 nm long and 65 nm at their widest diameter. On their external surfaces, they bear bristle-like filaments, each 3-4 nm thick and 25 nm long. Micronemes are translocated from a single Golgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 52 publications
7
108
0
3
Order By: Relevance
“…As shown by electron microscopy, the mitochondrion and the apicoplast are aligned asymmetrically in the P. falciparum merozoites along the same side as the microtubules (16,17). We found that, in addition to HA-PfROM1, other organelles in P. falciparum merozoites are also aligned on the same side of the parasite nucleus as the microtubules (Fig.…”
Section: Ha-pfrom1 Is In Close Proximity To the Merozoite Subpellicularsupporting
confidence: 59%
See 1 more Smart Citation
“…As shown by electron microscopy, the mitochondrion and the apicoplast are aligned asymmetrically in the P. falciparum merozoites along the same side as the microtubules (16,17). We found that, in addition to HA-PfROM1, other organelles in P. falciparum merozoites are also aligned on the same side of the parasite nucleus as the microtubules (Fig.…”
Section: Ha-pfrom1 Is In Close Proximity To the Merozoite Subpellicularsupporting
confidence: 59%
“…7, 8, and 10). We have shown that the location of the full-length PfROM1 is separate from AMA1 and EBA175, two proteins found in micronemes (17,23). The PfROM1 construct used here was similar to that used for localization of T. gondii ROM1 (10).…”
Section: Discussionmentioning
confidence: 93%
“…55 Micronemes are round, proteindense, membrane-bound organelles that have been shown to contain proteins secreted through their ducts near the apical end. 56,57 The ookinete pellicle includes the parasite plasma membrane, the inner membrane complex, and subpellicular microtubules. 35 The method presented here consistently produced large quantities of sexual stage forms of the human malaria parasite P. falciparum .…”
Section: Ultrastructural Analysis Of P Falciparum Sexual Stage Parasmentioning
confidence: 99%
“…This result indicates that molecules other than the parasite Duffy binding protein family are exposed by enzyme treatment to form the junction between Duffy negative human erythrocytes and P. knowlesi merozoites. One of the possible junction-forming molecules is apical merozoite antigen 1 (AMA1), which is found in the micronemes (4). Half of the cytoplasmic domain of AMA1 is highly conserved in all Plasmodium species, suggesting a role for signaling or interaction with the actin-myosin motor once the extracellular domain is engaged.…”
Section: T He Complex Multistep Process Of Invasion Of Erythrocytes Bymentioning
confidence: 99%